2020
DOI: 10.1186/s12912-020-00516-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurses’ perception about the care needs of patients with COVID-19: a qualitative study

Abstract: Background COVID-19 is a new disease affecting and killing a large number of people across the world every day. One way to improve health care for these patients is to recognize their needs. Nurses, as a large population of health care staff, can be rich sources of information and experience on patients’ care needs. Therefore, the aim of this study was to explore nurses’ perception about the care needs of patients with COVID-19. Methods The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 33 publications
7
70
2
1
Order By: Relevance
“…HCPs, due to prolonged work shifts, isolation, fear of being infected or of infecting others, and distress over the loss of many patients and colleagues [23,24], experienced unparalleled COVID-19-related stress, emotional pain, insomnia, exhaustion, job dissatisfaction [25][26][27], and depressive symptoms [28], which are expected to increase up to several years after the outbreak [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…HCPs, due to prolonged work shifts, isolation, fear of being infected or of infecting others, and distress over the loss of many patients and colleagues [23,24], experienced unparalleled COVID-19-related stress, emotional pain, insomnia, exhaustion, job dissatisfaction [25][26][27], and depressive symptoms [28], which are expected to increase up to several years after the outbreak [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during the SARS and Middle East respiratory syndrome (MERS) outbreaks in the past, many nurses avoided patient care or left their jobs because of fear (Chang et al., 2006; Chen et al., 2005; Maunder, 2004). Further, a qualitative study of nurses providing care for COVID‐19 patients showed that they experience psychological problems such as anxiety and hopelessness (Galehdar et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, the importance of nursing care has become even more visible. The fear of death was reported to be a stressful and bothersome factor for patients with COVID-19 (Galehdar et al 2020 ). Spiritual care is a process of helping patients cope with stressful times.…”
Section: Discussionmentioning
confidence: 99%